PENGARUH ETIKA KEPEMIMPINAN, FUNGSI BADAN PENGAWAS, TINGKAT PEMAHAMAN AKUNTANSI TERHADAP KUALITAS PELAPORAN KEUANGAN LPD DI KOTA DENPASAR - Ni Nyoman Ari Novarini; Desak Ayu Sriary Bhegawati (Politeknik Ubaya, 2021)
Abstract Village Credit Institutions are microfinance institutions that reflect the existence of a community in society based on the principles of Balinese customary law. There are 4 problems with the hypothesis of this study, namely leadership ethics has a positive effect on the quality of financial reporting, the function of the Supervisory Body has a positive effect on the quality of financial reporting, Work experience has a positive effect on the quality of financial reporting. The level of accounting comprehension has a positive effect on the quality of financial reporting. Sampling of this study used saturated sampling with all 35 LPD units studied in Denpasar City. The analytical tool used in this research was Multiple Linear Regression. , the results of the study showed that Leadership Ethics, the function of the supervisory body, and the level of accounting understanding have a positive effect on the quality of financial reports at LPDs in Denpasar City. While work experience has no effect on the quality of financial reports at LPDs in Denpasar City. Improving the performance of LPD managers, especially the chairman, must prioritize leadership ethics. In addition, the function of the supervisory body is always improved and refers to procedures according to the rules for presenting financial statements. Accounting understanding also continues to be improved. Employee training continues to be improved because it provides more work roles for the LPDs so that the performance of the Denpasar City LPD continues to increase. Keyword : Quality of Financial Statements, Leadership Ethics, Supervisory Body Functions, Level of Accounting Understanding